(untitled) (Fiep Bulletin - online, 2014)
The Encephalic Vascular Accident is about a neurological affection that sometimes incapacitates the person, and can cause innumerable complications in the patient life. The therapeutics techniques are always improved and renewed, in order to prevent such complications and to maximize the independence of these patients in their daily life activities. The neural mobilization is a relatively new technique that looks to keep or to restore the movement and the elasticity of the nervous system. The proposal of this study is based on mobilizing the nervous system of the hemiplegic superior member of individuals that had suffered VEA, through the ULNT 1 test, and evaluating the immediate influence in the plantar pressure distribution through the electronic baropodometry, analyzing the plantar pressures before and after the test. The present study had utilized 12 individuals who were arbitrarily selected, with average equal 59±72. The gotten results had presented variations in the plantar pressures between the hemiplegics members and the non-hemiplegics members, changing theirself in an unpredictable way after the test application of neural mobilization for superior member ULNT 1, being that some individuals had transfered pressure to the opposing member, whereas others had redistributed the pressure in the plantar regions of the same member, also happening in the hemiplegic member. Although, these changes have been observed, they had not been statistically significant with p>0,05.